Technology and innovation report 2010 : (United nations, 2010)
UNCTAD’s Technology and Innovation Report 2010 focuses on the technological challenges that small-holder farmers in developing countries, especially sub-Saharan Africa, face in increasing agricultural productivity. It outlines the agricultural sector’s challenges and the roles of technology and innovation in rising production and the income of small-holder farmers. And it describes readily available technologies that can be applied now to improve soils, manage water shortages and resist drought.